2014
DOI: 10.1590/bjb.2014.0084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Oligoryzomys nigripes and O. flavescens by RAPD and genetic diversity in O. nigripes (Rodentia, Cricetidae)

Abstract: The genus of Oligoryzomys includes species of small size, morphologically similar, which may impede taxonomic identification, mainly between O. flavescens (Waterhouse, 1837) and O. nigripes (Olfers, 1818). The main objective of this work was to investigate whether the RAPD markers are capable of genetically differentiating the specimens O. nigripes and O. flavescens, coming from Rio Grande do Sul (RS) and Santa Catarina (SC) states, and also to estimate the genetic variability among populations of O. nigripes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a large-scale analysis based on divergence patterns using cyt-b sequences of several non-volant mammals from the Amazon basin, Patton et al (2000) found no evidence to support that the Juruá River, one of the main affluent rivers of the Amazon River, would act as an important barrier, suggesting that large rivers could be more likely to be crossed than expected. In a study based on RAPD (Random Amplified Polymorphic DNA) data, the cricetid rodent Oligoryzomys showed no structure at both banks of the Uruguay River at the proximities of the headwater (Mossi et al, 2014), indicating that it would not be acting as a strong barrier to gene flow. Regarding tuco-tucos, the diversification along but not across rivers demonstrated that C. torquatus may have been able to cross the also large Ibicuí, Vacacaí and Jacuí rivers during a period of dry climate (Roratto et al, 2015).…”
Section: The Uruguay River As a Barriermentioning
confidence: 99%
“…In a large-scale analysis based on divergence patterns using cyt-b sequences of several non-volant mammals from the Amazon basin, Patton et al (2000) found no evidence to support that the Juruá River, one of the main affluent rivers of the Amazon River, would act as an important barrier, suggesting that large rivers could be more likely to be crossed than expected. In a study based on RAPD (Random Amplified Polymorphic DNA) data, the cricetid rodent Oligoryzomys showed no structure at both banks of the Uruguay River at the proximities of the headwater (Mossi et al, 2014), indicating that it would not be acting as a strong barrier to gene flow. Regarding tuco-tucos, the diversification along but not across rivers demonstrated that C. torquatus may have been able to cross the also large Ibicuí, Vacacaí and Jacuí rivers during a period of dry climate (Roratto et al, 2015).…”
Section: The Uruguay River As a Barriermentioning
confidence: 99%
“…All DNA was extracted and quantified at the biochemistry and molecular biology laboratory of URI. Seven protocols for DNA extraction were selected from the literature, whose methodologies had previously been described for fish species or whose parameters were similar to those intended to be analyzed in this work, such as the same extraction conditions or target-tissues (Doyle and Doyle, 1987;Medrano et al, 1990;Whitmore et al, 1992;Aljanabi and Martinez, 1997;Faleiro et al, 2003;Barrero et al, 2008;Mossi et al, 2014). An eighth protocol was proposed and evaluated, combining the variables that presented better results in the extraction of H. commersoni DNA in each of the seven tested protocols.…”
Section: Dna Extractionmentioning
confidence: 99%